"Capacity", "best interests", "will and preferences" and the UN Convention on the Rights of Persons with Disabilities. Issue 1 (2nd January 2019) - Szmukler, George
Abstract : The United Nations (UN) Convention on the Rights of Persons with Disabilities (CRPD) is the most up‐to‐date international legal instrument concerning the rights of persons with disabilities. Such persons are taken to include those with serious mental disorders. According to an authoritative interpretation of a crucial Article (Article 12 ‐ Equal recognition before the law) by the UN CRPD Committee, involuntary detention and treatment of people with mental health disabilities are prohibited under the Convention. Both conventional mental health law and "capacity‐based" law are deemed to violate the Convention. However, some other UN bodies are not in full agreement (for example, the UN Human Rights Committee and the Subcommittee on Prevention of Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment), while others are less explicitly absolutist (for example, the Human Rights Council). Furthermore, strong criticisms of the position of the CRPD Committee have been mounted from a number of academic quarters. These criticisms center on whether the role of a person's ability to make a decision can be ignored, no matter the circumstances. Much of the above debate turns on the concept of "legal capacity" and the now often‐repeated precept that one must always respect the "will and preferences" of the person with a disability. However, "will and preferences" remains undefined. In this paper, I offer an analysis of "will and preferences" that can clarify interventions that may be acceptable or non‐acceptable under the terms of the UN Convention.